Peningkatan Efisiensi Dan Mutu Packaging Melalui Pemanfaatan Continuous Band Sealer Pada UMKM Rengginang - Susanti Dwi Ilhami; Daniel Alfa Puryono; Damayanti Damayanti (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Rengginang is one of the leading products of Rembang Regency. One of the sub-districts that produces rengginang is Banggi sub-district. Rengginang enthusiasts are increasing rapidly both from domestic and outside the city. The problem faced is that regginang packaging is prone to leakage so that product quality decreases. In addition, the sealing process that has been carried out takes a long time so that it is less efficient when there is a spike in demand. Therefore, technology is needed to improve the efficiency and quality of rengginang product packaging. Community service activities aim to produce rengginang packaging that has high quality and time efficiency. The stages of community service activities include planning, implementation, and evaluation. The results of the implementation of community service activities are that the sealing of the packaging is tighter so that the quality of the packaging can be better and is not prone to leaks. In addition, the sealing process for one packaging is only need just 0.7second so time efficiency is much better.